Mejoramiento genético. Mejoramiento de caracteres. Variabilidad de hibridzación interespecífica - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The objectives of the collaborative project between CIAT and the Faculty of Agronomy of Gembloux (Belgium) are focused on the improvement of Phaseolus vulgaris through a program of wide crosses with other Phaseolus species. Several species were evaluated and used in crosses, mainly of the group of P. coccineus. In addition, several accessions of the subspecies polyanthus were evaluated in Popayan, Colombia, for their reaction to Ascochyta leaf spot, and within the great lakes project, 22 accessions of the subspecies coccineus and polyanthus were evaluated in Rwanda for their reaction to the bean fly. The results of these trials are presented in table form. (CIAT)